If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 87 + 98 + 90 + 85 = x Combine like terms: 87 + 98 = 185 185 + 90 + 85 = x Combine like terms: 185 + 90 = 275 275 + 85 = x Combine like terms: 275 + 85 = 360 360 = x Solving 360 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 360 + -1x = x + -1x Combine like terms: x + -1x = 0 360 + -1x = 0 Add '-360' to each side of the equation. 360 + -360 + -1x = 0 + -360 Combine like terms: 360 + -360 = 0 0 + -1x = 0 + -360 -1x = 0 + -360 Combine like terms: 0 + -360 = -360 -1x = -360 Divide each side by '-1'. x = 360 Simplifying x = 360
| -4(5x+2)=52 | | 8x+4(-4x+7)=34-8x | | x-9/7=3x | | x=43+86+51 | | 13m-21=9m-6 | | 7(2x-3)-3(5x+6)=-4(-3x+5)+5(-4x+5) | | 12-7b=18-9b | | 4x+8y=-44 | | ax+5=bx-cforx | | 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 | | 10-3c=10+9c | | 1x+7=2x+3 | | 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 | | 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 |